2022
DOI: 10.1098/rspb.2022.1718
|View full text |Cite
|
Sign up to set email alerts
|

Protection from fishing improves body growth of an exploited species

Abstract: Hunting and fishing are often size-selective, which favours slow body growth. In addition, fast growth rate has been shown to be positively correlated with behavioural traits that increase encounter rates and catchability in passive fishing gears such as baited traps. This harvest-induced selection should be effectively eliminated in no-take marine-protected areas (MPAs) unless strong density dependence results in reduced growth rates. We compared body growth of European lobster ( Homarus gammarus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…These results are consistent with other metrics of fish community health inside of MPAs, such as increases in abundance and biomass (Carr et al, 2021;Hamilton et al, 2021). And the increases in bold behavior of fish inside of MPAs should lead to increases in the other metrics of fish community health (Biro and Post, 2008;Sørdalen et al, 2022). As such, FID represents a new and useful tool for evaluating the effectiveness of the MPA network in Southern California.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with other metrics of fish community health inside of MPAs, such as increases in abundance and biomass (Carr et al, 2021;Hamilton et al, 2021). And the increases in bold behavior of fish inside of MPAs should lead to increases in the other metrics of fish community health (Biro and Post, 2008;Sørdalen et al, 2022). As such, FID represents a new and useful tool for evaluating the effectiveness of the MPA network in Southern California.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that fish with traits correlated to increased foraging behavior, such as greater boldness and activity rates, are more likely to be caught by fishermen (Biro and Post, 2008). It has also been observed that populations outside of protected areas begin to evolutionarily self-select traits that lead to slower growth rates, while those inside MPAs exhibit behaviors leading to faster growth (Sørdalen et al, 2022). Larger fish, in turn, lead to more and greater viability of offspring (Qvarnström and Price, 2001;Birkeland and Dayton, 2005;Pew Charitable Trusts, 2016), allowing populations to recover to pre-fishing levels.…”
Section: Introductionmentioning
confidence: 99%
“…Most empirical research on how protected areas could mitigate harvest‐induced evolution has focused on marine ecosystems (Hutchings & Fraser, 2008 ; Hutchings & Kuparinen, 2020 ). These studies suggest that marine protected areas can sometimes preserve or restore abundance, age structure and phenotypic trait distribution of exploited fish and invertebrate populations (Gillespie & Vincent, 2019 ; Sørdalen et al, 2020 , 2022 , synthesized by Lester et al, 2009 ; Baskett & Barnett, 2015 ). For instance, Russ et al, 2004 found that a no‐take reserve in the Philippines increased density and harvest of surgeonfish ( Acanthuridae spp) and jacks ( Carangidae spp) in nearby exploited areas.…”
Section: Introductionmentioning
confidence: 99%